Training systems improved agronomic characteristics and quality of ‘Niagara Rosada’ table grapes - Pimentel Junior, Adilson [UNESP]; Domingues Neto, Francisco José [UNESP]; Basílio, Letícia Silva Pereira [UNESP]; Monteiro, Gean Charles [UNESP]; Lima, Giuseppina Pace Pereira [UNESP]; Tecchio, Marco Antonio [UNESP] (FapUNIFESP (SciELO), 2023)
Vines are highly responsive to agricultural management techniques, such as training systems. Three training systems, i.e., conventional, high, and double training, for the ‘Niagara Rosada’ vine were studied considering aspects related to the yield, physicochemical, and antioxidant characteristics of the grapes. The experiment was carried out during two seasons (2017 and 2018), and the vines grafted on IAC 572 Jales. The training systems did not influence the fruit production per vine and yield of the ‘Niagara Rosada’ table grape, but some improvements were observed, such as a greater number of berries per bunch in vines managed in the conventional training systems and a higher fresh mass of berries when cultivated in the high and double training systems. Grapes from the double training system had higher soluble solids contents, an important sensorial characteristic in table grapes. The high training system, in turn, provided ‘Niagara Rosada’ table grapes with a greater content of bioactive compounds (e.g., phenolic compounds, flavonoids, and anthocyanins) and antioxidant activity.
Keywords: antioxidant activity; bioactive compounds; vertical shoot positions; Vitis spp